FORM ELEMENTS OF NATIONAL PRIDE BY CHILDREN IN HISTORICAL MONUMENTSIN PRESCHOOL EDUCATIONAL ORGANIZATION - Rajabova Nafosat; O’rinova Nargiza (Journal Park Publishing, 2022)
This article discusses the content of the upbringing of preschool children in preschool institutions on the basis of national values and its social basis
Keywords: national values; cultural and historical heritage; spiritual upbringing